PENGARUH ALAT PERLENGKAPAN ORGANISASI KOPERASI (APOK) DAN PARTISIPASI ANGGOTA TERHADAP KEBERHASILAN USAHA KOPERASI DI KOTA PEKANBARU - Hendriani, Susi; Ningsih, Dewita Suryati; Fitri, Kurniawaty (Jurnal Tepak Manajemen Bisnis, 2015)
The development of cooperative institutions sufficiently increased, but the realities of howcooperative they are faced with various problems, among others: the ability of management to managethe cooperative is still much to be improved, the weak aspects of managerial and entrepreneurial skillswithin the cooperative, the lack of qualified managers of cooperatives, the lack of effective programs -Program training for cooperative management, the cadre system is still a weakness in terms ofcooperative management, regulatory bodies from the member considered less professional inperforming their duties.In other words, that the success of cooperative efforts in addition affected by Apok namely Meeting ofMembers, Officers and Trustees, was also influenced by the active participation of its members.This study aimed to determine the effect of tools and equipment to the success of the cooperativeorganization of cooperative efforts in the city of Pekanbaru. By using the methods of descriptiveanalysis and qualitative approaches. Data collection techniques include interviews, observation,documentation studies, literature studies.The results showed that the implementation of the annual meeting of members of the cooperative inPekanbaru city is still relatively low, the regulatory body of the cooperative members have largely hadhigh educational background (S1 and S2), but has a lot of diversity in the focus of concentration, aswell as cooperative management.The majority of the board is also an employee or staff wherecooperatives that are so lacking focus in the management of the cooperative. Participation ofcooperative members are already well as the participation of members in paying off the principal andmandatory savings, utilizing business units in cooperative, active members in a meeting and gathering,monitoring the course of the cooperative by members also good.The recommendations can be given, among others, the necessary consistency of each cooperative tohold an annual meeting of members within a minimum period that has been specified in theCooperative Act, providing education and training specific to the regulatory body that carried out bythe service cooperative, so the results more effectively so as to contribute significantly to the success ofcooperative efforts, the board is expected to increase the knowledge and skills by learning more indepthknowledge of the various cooperative either by his own efforts, by reading books aboutcooperatives and training or courses in the field of cooperatives. Participation cooperative membersshould be increased because of the success of the cooperative effort is highly dependent on theparticipation of its members.Keywords : Member Meeting, Administrator, Board of Supervisors, Cooperative, Pekanbaru.